Асимптотика ограниченных управлений в оптимальных сингулярных параболических задачах - Капустян, В.Е. (Український математичний журнал, 1993)
A complete asymptotical solution is constructed and justified for optimal singular parabolic problems with constraint control and complete degeneration of the differential part of the operator.